Collagen synthesis after laser skin resurfacing of the periocular skin - Beltram, Matej (Zdravniški vestnik, 2010)
Background: Laser skin resurfacing (LSR) is a procedure in oculoplastic surgery, used for the reduction of periocular rhytides. Clinical effect of thereduction of rhytides is achieved through remodeling of skin collagen. Collagen synthesis after LSR has been evaluated both by histological examination and analysis of collagen gene expression in up-to-date studies. However, these studies are comparable only to a lesser degree due to differences between examinators and histologic criteria. The goal of this study was to assess the usefulness of in situ hybridization (ISH) analysis of type I collagen gene expression after Er:YAG LSR. Patients and methods: Eyelidskin of 9 volunteer patients has been treated by Er:YAG laser with LSR parameters. Twenty-one days after the treatment the skin was excised as part of the blepharoplasty procedure. For ISH, a pro alpha (I) collagen antisense copy-DNA (cDNA) probe was designed. We prepared tissue sections and hybridizedthem with the radiolabelled cDNA probe. We used untreated skin areasfrom the same skin samples as a control group. Results: We determined andstatistically analyzed the levels of pro alpha (I) collagen gene expressionin the samples collected, which varied significantly between the treated and untreated skin. Conclusions: In situ hybridization analysis is a useful method in determining the site and rate of collagen gene expression after Er:YAG LSR. We suggest that this method is useful in determining the amount of collagen synthesis after laser skin resurfacing and is less observer-dependent than histological evaluation alone.
Keywords: Biosynthesis; Blefarospazem; Blepharospasm; Collagen; Gene Expression; Genetics; Gensko izražanje; Kolagen; koža vek; Laser Surgery; Laserska kirurgija; Rhytidoplasty; Ritidoplastika; sinteza kolagena; Surgery; veke